CRUSTAL STRUCTURE OF THE CONTINENTAL MARGIN OF KOREA IN THE EAST SEA (JAPAN SEA) FROM DEEP SEISMIC SOUNDING DATA: EVIDENCE FOR RIFTING AFFECTED BY THE HOTTER THAN NORMAL MANTLE - Kim H.J.; Jou H.T.; Cho H.M.; Bijwaard H.; Sato T.; Hong J.K.; Yoo H.S.; Baag C.E. (My University, 2003)
Despite the various opening models of the southwestern part of the East Sea (Japan Sea) between the Korean Peninsula and the Japan Arc, the continental margin of the Korean Peninsula remains unknown in crustal structure. As a result, continental rifting and subsequent seafloor spreading processes to explain the opening of the East Sea have not been adequately addressed. We investigated crustal and sedimentary velocity structures across the Korean margin into the adjacent Ulleung Basin from multichannel seismic (MCS) reflection and ocean bottom seismometer (OBS) data. The Ulleung Basin shows crustal velocity structure typical of oceanic although its crustal thickness of about 10 km is greater than normal. The continental margin documents rapid transition from continental to oceanic crust, exhibiting a remarkable decrease in crustal thickness accompanied by shallowing of Moho over a distance of about 50 km. The crustal model of the margin is characterized by a high-velocity (up to 7.4 km/s) lower crustal (HVLC) layer that is thicker than 10 km under the slope base and pinches out seawards. The HVLC layer is interpreted as magmatic underplating emplaced during continental rifting in response to high upper mantle temperature. The acoustic basement of the slope base shows an igneous stratigraphy developed by massive volcanic eruption. These features suggest that the evolution of the Korean margin can be explained by the processes occurring at volcanic rifted margins. Global earthquake tomography supports our interpretation by defining the abnormally hot upper mantle across the Korean margin and in the Ulleung Basin.
Keywords: KOREAN MARGIN; DEEP SEISMIC SOUNDING; TOMOGRAPHY; CRUSTAL STRUCTURE; MAGMATIC UNDERPLATING